O princípio da função social no processo de recuperação judicial, à luz da jurisprudência das Câmaras Especializadas do Tribunal de Justiça do Estado do Rio Grande do Sul - Silveira, Arthur Alves (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation focuses on the analysis of the social function principle (princípio da função social) as applied in the process of judicial recovery (recuperação judicial), resulting in theoretical and empirical contours, in the investigation of the implications of this principle, and the delimitation of the company’s judicial recovery process, as stipulated by Law n.o 11.101/2005. Given the importance that business activity has in society, we sought to identify how a general norm is employed within the process of business recovery. To achieve the expected results, the methodology encompassed a bibliographic research, seeking in the specialized doctrine the foundations and bases for the themes this dissertation develops, as well as an empirical investigation into the contents of the case law (jurisprudência) presented by the Rio Grande do Sul State Court’s 5th and 6th Chambers, which specialize in judicial recovery. In this research, it was possible to ascertain that the social function, in the judicial recovery process, is closely linked to the company preservation principle (princípio de preservação da empresa), so much so that the doctrine and case law eventually demonstrate this connection, using material requirements for the application of the social function principle in the process of judicial recovery. The compilation provided by this dissertation led to objective results that demystify, in a way, the principle of social function in the Brazilian legal system, within the research’s scope.
Keywords: Função social; Recuperação judicial; Princípios; Preservação da empresa; Repertório jurisprudencial; Social function; Judicial recovery; Legal principles; Company preservation; Case law compilation; ACCNPQ::Ciências Sociais Aplicadas::Direito